2009
DOI: 10.1056/nejmoa0901836
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Safety in the Longitudinal Assessment of Bariatric Surgery

Abstract: Background The risks of bariatric surgical procedures must be balanced against their benefits and require further characterization. Methods Longitudinal Assessment of Bariatric Surgery-1 (LABS-1) was a prospective, multi-center observational study of 30-day outcomes in consecutive patients undergoing bariatric surgical procedures at 10 clinical sites in the United States (2005-2007). A composite endpoint of 30-day major adverse outcomes (death; venous thromboembolism; percutaneous, endoscopic, or operative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
283
4
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,223 publications
(308 citation statements)
references
References 22 publications
12
283
4
9
Order By: Relevance
“…104 The Longitudinal Assessment of Bariatric Surgery (LABS) study subsequently reported a similarly low 30-day mortality rate (0.3 %) among 4776 patients. 105 Immediate-and long-term perioperative morbidity rates for bariatric surgery are lower than might be expected for this medically comorbid population; the LABS Consortium reported a 4.3% incidence of major adverse events in the early postoperative period. Although these reports are encouraging, a number of complications associated with bariatric surgery are potentially fatal and merit careful consideration.…”
Section: Complications Of Surgerymentioning
confidence: 99%
“…104 The Longitudinal Assessment of Bariatric Surgery (LABS) study subsequently reported a similarly low 30-day mortality rate (0.3 %) among 4776 patients. 105 Immediate-and long-term perioperative morbidity rates for bariatric surgery are lower than might be expected for this medically comorbid population; the LABS Consortium reported a 4.3% incidence of major adverse events in the early postoperative period. Although these reports are encouraging, a number of complications associated with bariatric surgery are potentially fatal and merit careful consideration.…”
Section: Complications Of Surgerymentioning
confidence: 99%
“…A large multicentre, observational study of 4776 patients with a median BMI of 46.5 kg/m 2 undergoing a bariatric surgical procedure reinforced the feasibility of surgery in obese individuals and demonstrated low rates of morbidity and mortality within 30 days of surgery. 16 This study highlighted the importance of risk stratification and particularly recognized the increased risk conferred by a history of deep venous thrombosis, pulmonary embolus, obstructive sleep apnea and impaired overall functional status.…”
Section: Discussionmentioning
confidence: 98%
“…The 30-day perioperative mortality rate for gastric bypass (up to 0.4%) is at least four times higher when compared to the gastric band (up to 0.1%). 7 At two years, the gastric band mortality rate (0.0%) continues to be lower compared to the bypass (0.4%). 35 Recipients of the gastric bypass and sleeve are also at risk of nutritional deficiencies.…”
Section: Safety Of Bariatric Surgerymentioning
confidence: 97%
“…Most procedures are generally performed laparoscopically as observed in the Longitudinal Assessment of Bariatric Surgery (LABS) study. 7 Bariatric surgery is not only effective in weight reduction, it also results in greater improvement and remission of T2D. The most common procedures carried out in the National Health Service (NHS) are laparoscopic adjustable gastric banding (LAGB), laparoscopic Roux-en-Y gastric bypass (RYGB) and laparoscopic sleeve gastrectomy (LSG).…”
mentioning
confidence: 99%